2018
DOI: 10.1038/s41598-018-24446-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular markers of inflammation and serum lipid levels in HIV-infected patients with undetectable viremia

Abstract: Patients successfully treated for HIV infection still have an increased risk for cardiovascular morbidity and mortality, which might be related not only to traditional risks, but also to inflammation and dyslipidemia. We examined the relationship of serum lipid levels with plasma biomarkers of inflammation using a composite inflammatory burden score (IBS) based on individual (>75th percentile) measurements from the following seven markers: CD40L, tPA, MCP-1, IL-8, IL-6, hCRP and P-selectin. IBS was categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…The most commonly measured biomarkers included IL-6 [29, 53, 56, 97–108], highly sensitive CRP [7, 28, 98, 99, 101–104, 106, 108, 109] and D-dimer levels [7, 28, 98, 99, 101–104, 106, 108, 109]. In addition, a number of studies measured markers of endothelial adhesion or activation, or both, including soluble intercellular adhesion molecule-1 and soluble vascular cell adhesion molecule-1 [7, 15, 17, 50, 97, 106–108, 110–112], monocyte activation (sCD163, sCD14, or changes in monocyte phenotype) [15, 28, 29, 50, 56, 96, 97, 100, 107–114], and platelet activation (expression of s- and p-selectin) [30, 33, 115]. Limitations exist in many studies examining biomarkers for CVD outcomes.…”
Section: Pathophysiological Mechanisms Associated With Development Ofmentioning
confidence: 99%
“…The most commonly measured biomarkers included IL-6 [29, 53, 56, 97–108], highly sensitive CRP [7, 28, 98, 99, 101–104, 106, 108, 109] and D-dimer levels [7, 28, 98, 99, 101–104, 106, 108, 109]. In addition, a number of studies measured markers of endothelial adhesion or activation, or both, including soluble intercellular adhesion molecule-1 and soluble vascular cell adhesion molecule-1 [7, 15, 17, 50, 97, 106–108, 110–112], monocyte activation (sCD163, sCD14, or changes in monocyte phenotype) [15, 28, 29, 50, 56, 96, 97, 100, 107–114], and platelet activation (expression of s- and p-selectin) [30, 33, 115]. Limitations exist in many studies examining biomarkers for CVD outcomes.…”
Section: Pathophysiological Mechanisms Associated With Development Ofmentioning
confidence: 99%
“…However, biomarkers of inflammation and immune activation such as CRP, microalbuminuria, cystatin C and soluble CD14 are elevated in HIV‐infected patients even when on cART , reflecting residual inflammatory/immune activation. Consistent with these findings, we did not find any correlation between the evaluated parameters and viral load or CD4 count, suggesting that, after viral suppression, the detrimental factors leading to atherothrombotic events are not completely normalized, and may reflect the excess CV risk observed in HIV‐infected patients even when successfully treated with ART .…”
Section: Discussionmentioning
confidence: 92%
“…This result emphasizes the additional effect of HIV related and individual components of MetS on the susceptibility to CVD mortality risk, at the absence of increased age. HIV infection, immune activation and inflammation are related to cardiovascular risk among the population, characterized by the complex interaction of systematic factors at all stages of HIV-infection progression [13, 16]. Likewise, both untreated HIV-infected and treated persons are adversely susceptible to CVD outcomes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al [59] showed a yearly increasing CVD risk among treated HIV-infected patients, establishing that the duration of ART exposure is strongly associated with CVD outcome. Višković et al [13] analyzed the association between the presence of CVD biomarkers and related HIV-infected patient characteristics. The results of their study showed a positive correlation between the duration of HIV infection and ART and the presence of CVD markers, with a median of 8 and 6 years respectively [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation